IMPLEMENTASI LAYANAN PAUD HOLISTIK TERINTEGRASI DI POS PAUD BAITURAHMAN KAMPUNG CIJAMBE DESA CINUNUK KECAMATAN CILEUNYI KABUPATEN BANDUNG - Sriningsih, Nining (PEDAGOGIA, 2014)
This research is intended to integrate the PAUD 1services in a service program of religion-based POS PAUD, which is scheduled every Monday to Friday from 09.00-10.00 AM and 03.30-04.30 PM. Collaborative action research is the method employed in this research and community service program. The results of this research and community service program are: (1) The establishment of religion-based PAUD service; (2) The formulation of hypothetic model of religion-based PAUD service named MULTIAGE INDIVIDUAL LEARNING SYSTEM (MILS), which focuses on playing material priority about Islamiyyah character building in order to create educated/insan kamil generation. Furthermore, the recommendation of this research are: (1) training for ustadzah in POS PAUD Baiturrahman is needed, especially in utilizing household waste as APE for early years children, developing Islamiyyah characters of the early years children, and playing activities as an intelligence device for the early years children; and (2) MILS socialization for the ustadzah in POS PAUD BAITURRAHMAN.Keyword : Central PAUD,Integrated Holistic,Central PAU Based on Religion, elarly chilehood.